2022
DOI: 10.1177/0958305x221115095
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy, economic, environmental, advanced exergy and exergoeconomic (extended exergy) analysis of hybrid wind-solar power plant

Abstract: Aiming to net-zero emissions, hybrid power generation through renewable means has gained substantial attention across the globe. Considering the stochastic nature of renewable energy resources, a comprehensive performance assessment is a must prior to project development. Present work is a novel multidimensional 6E analysis (energy, exergy, economic, environmental, advanced exergy, and exergoeconomic) to evaluate the performance of hybrid wind-solar energy systems. The analysis is performed using long-tern (41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Vertical axis wind turbines or bladeless wind turbines could be alternative plans for HPWESS that are operated on buildings or around people since the optional devices have merits like low noise and ease of installation and maintenance compared to HAWT. As for the generator of solar energy, energy and exergy analysis revealed that among all the components, the PV panels have the lowest conversion efficiency in HPWESS, which is far behind others' efficiency [61][62][63][64]. Advanced generators of solar energy that improve the photovoltaic conversion efficiency or use discarded thermal energy of insolation to generate additional power are expected to develop, which will promote the efficiency of the whole power system.…”
Section: Opportunities and Challenges For Hpwessmentioning
confidence: 99%
“…Vertical axis wind turbines or bladeless wind turbines could be alternative plans for HPWESS that are operated on buildings or around people since the optional devices have merits like low noise and ease of installation and maintenance compared to HAWT. As for the generator of solar energy, energy and exergy analysis revealed that among all the components, the PV panels have the lowest conversion efficiency in HPWESS, which is far behind others' efficiency [61][62][63][64]. Advanced generators of solar energy that improve the photovoltaic conversion efficiency or use discarded thermal energy of insolation to generate additional power are expected to develop, which will promote the efficiency of the whole power system.…”
Section: Opportunities and Challenges For Hpwessmentioning
confidence: 99%